2021
DOI: 10.1038/s41467-021-23379-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular landscape and subtype-specific therapeutic response of nasopharyngeal carcinoma revealed by integrative pharmacogenomics

Abstract: Nasopharyngeal carcinoma (NPC) is a malignant head and neck cancer type with high morbidity in Southeast Asia, however the pathogenic mechanism of this disease is poorly understood. Using integrative pharmacogenomics, we find that NPC subtypes maintain distinct molecular features, drug responsiveness, and graded radiation sensitivity. The epithelial carcinoma (EC) subtype is characterized by activations of microtubule polymerization and defective mitotic spindle checkpoint related genes, whereas sarcomatoid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 94 publications
2
43
0
Order By: Relevance
“…Of note, our previous report had already found that malignant spindle cells correlated closely with EMT, and should be the more aggressive subtype in NPC (Luo et al 2012a). Interesting, Ding RB et al has recently also showed that these sarcomatoid cells exhibited enriched EMT and invasion promoting genes (Ding et al 2021). Taken together, our results imply that nuclear LMP1 may promote greatly the dynamic progression of NPC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Of note, our previous report had already found that malignant spindle cells correlated closely with EMT, and should be the more aggressive subtype in NPC (Luo et al 2012a). Interesting, Ding RB et al has recently also showed that these sarcomatoid cells exhibited enriched EMT and invasion promoting genes (Ding et al 2021). Taken together, our results imply that nuclear LMP1 may promote greatly the dynamic progression of NPC.…”
Section: Discussionsupporting
confidence: 76%
“…2012a). Interesting, Ding RB et al has recently also showed that these sarcomatoid cells exhibited enriched EMT and invasion promoting genes (Ding et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…NPCs are histologically classified into the following four subtypes based on morphologic characteristics: epithelial carcinoma (EC), sarcomatoid carcinoma (SC), mixed sarcomatoid-epithelial carcinoma (MSEC), and squamous cell carcinoma (SCC). 12 , 13 Our case is EC subtype, most of the tumor regions are identified with round epithelial cells and vesicular nuclei phenotype appearance. Figure 2(a) and ( m ) represent histological view of the primary and recurrent tumors, which shows similar morphologic traits.…”
Section: Case Presentationmentioning
confidence: 77%
“…sarcomatoid-epithelial carcinoma (MSEC), and squamous cell carcinoma (SCC). 12,13 Our case is EC subtype, most of the tumor regions are identified with round epithelial cells and vesicular nuclei phenotype appearance. Figure 2(a) and (m) represent histological view of the primary and recurrent tumors, which shows similar morphologic traits.…”
Section: Differential Diagnosismentioning
confidence: 87%
“…Nasopharyngeal carcinoma (NPC), developing in the nasopharynx, is endemic in Southeast Asia and recognized as a head and neck malignancy. 1 The World Health Organization (WHO) grouped NPC into keratinizing squamous cell carcinoma, non-keratinizing squamous carcinoma, and undifferentiated carcinoma subtypes. 2 Risk factors associated with NPC are genetics, Epstein-Barr Virus(EBV), dietary factors, and smoking.…”
Section: Introductionmentioning
confidence: 99%